2020
DOI: 10.1016/j.btre.2020.e00514
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transient expression of functional human vascular endothelial growth factor in Nicotiana benthamiana and characterization of its biological activity

Abstract: Highlights Growth factors play a crucial role in wound healing. Plant-produced human vascular endothelial growth factor (hVEGF) induces the keratinocyte cells migration. The plant-produced hVEGF has shown potential as a wound healing agent in drug and cosmetic industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Because the investment cost and time for phase 1 cGMP manufacturing of plant expression system are comparatively cost-effective (7.5- to 10-fold) and faster (<6 months) than mammalian expression system, the plant-production platform might be an alternative platform for the production of many biopharmaceutical products. The use of plant expression systems for the production of pharmaceutically important proteins ( Bulaon et al, 2020 ; Hanittinan et al, 2020 ), vaccines ( Marsian et al, 2017 ; Rosales-Mendoza et al, 2017 ), diagnostic reagents ( Rattanapisit et al, 2021 ), and antibodies ( Kopertekh et al, 2019 ; Hurtado et al, 2020 ; Rattanapisit et al, 2020 ) were documented. In addition, the prior studies reported that the generation of plant-made protective immunogen and therapeutic antibodies ( Dent et al, 2016 ; Rattanapisit et al, 2019a , b ; Nessa et al, 2020 ; Yiemchavee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the investment cost and time for phase 1 cGMP manufacturing of plant expression system are comparatively cost-effective (7.5- to 10-fold) and faster (<6 months) than mammalian expression system, the plant-production platform might be an alternative platform for the production of many biopharmaceutical products. The use of plant expression systems for the production of pharmaceutically important proteins ( Bulaon et al, 2020 ; Hanittinan et al, 2020 ), vaccines ( Marsian et al, 2017 ; Rosales-Mendoza et al, 2017 ), diagnostic reagents ( Rattanapisit et al, 2021 ), and antibodies ( Kopertekh et al, 2019 ; Hurtado et al, 2020 ; Rattanapisit et al, 2020 ) were documented. In addition, the prior studies reported that the generation of plant-made protective immunogen and therapeutic antibodies ( Dent et al, 2016 ; Rattanapisit et al, 2019a , b ; Nessa et al, 2020 ; Yiemchavee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, plant expression systems have gained major interests in the making of recombinant proteins due to the economical production costs in upstream processes, rapid scalability employing versatile growth conditions, pathogen free with low risks of contamination [3,17]. Nicotiana genus has been widely used establishing a history in the production of heterologous recombinant proteins that include antibodies [18][19][20], vaccines [21,22], enzymes [23,24], growth factors [25][26][27], diagnostics [28], anti-microbial peptides [29] and other value-added products [30] because of the ease in genome manipulation and fast growth rate [31,32]. The transient expression by agroinfiltration was adopted in plants to produce various proteins for therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, abundant literature reveals that plant-based expression of recombinant proteins is a promising technology (Shanmugaraj and Phoolcharoen, 2021) and was successful in the expression of virus-like-particles (VLP's) (Ward et al, 2021), monoclonal antibodies (Shanmugaraj et al, 2020b;Swope et al, 2022), antigens (Rattanapisit et al, 2020b), growth factors (Bulaon et al, 2020;Hanittinan et al, 2020;Rattanapisit et al, 2020a), enzymes (Fox, 2012) due to the advantages in terms of high reproducibility, scalability in short time with lower contamination menace (Shanmugaraj et al, 2020a). Accordingly, the present study focuses on the recombinant production of anti-IgE antibod y by Agrobacterium mediated transformation in N. benthamiana host system.…”
Section: Discussionmentioning
confidence: 99%